Synthesis of New Pyrazolines Derivatives from Coumarine Compounds - W. Gh-Bedewy; O. Salih; A. Ahmad (College of Education for Pure Sciences, 1999)
Abstract The present work includes preparation of series of chalcones and condensation of these chalcones with a series of prepared coumarin hydrazides in acidic medium to afford the new pyrazolines. Physical and available spectral were used to confirm structures